2016
DOI: 10.1155/2016/9480843
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Utility of Bronchoalveolar Lavage Pepsin in Diagnosis of Gastroesophageal Reflux among Wheezy Infants

Abstract: Background. There is no gold standard test for diagnosis of gastroesophageal reflux disease (GERD) associated infantile wheezing. Objectives. To evaluate the value of bronchoalveolar lavage (BAL) pepsin assay in diagnosis of GERD in wheezy infants. Methods. Fifty-two wheezy infants were evaluated for GERD using esophageal combined impedance-pH (MII-pH) monitoring, esophagogastroduodenoscopy with esophageal biopsies, and BAL pepsin. Tracheobronchial aspirates from 10 healthy infants planned for surgery without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 28 publications
0
13
1
2
Order By: Relevance
“…Numerous biomarkers have been proposed for the diagnosis of aspiration into lower airway, including lipid laden macrophages and BAL pepsin. However, most of these parameters are unreliable . In our investigation, NI‐orally fed subjects had a lower airway microbiota enriched with the oral commensal Veillonella , suggesting that this taxon may be a marker for aspiration in this group.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous biomarkers have been proposed for the diagnosis of aspiration into lower airway, including lipid laden macrophages and BAL pepsin. However, most of these parameters are unreliable . In our investigation, NI‐orally fed subjects had a lower airway microbiota enriched with the oral commensal Veillonella , suggesting that this taxon may be a marker for aspiration in this group.…”
Section: Discussionmentioning
confidence: 99%
“…However, these results should be interpreted with caution because of emerging data on the low sensitivity and specificity of pepsin in bronchoalveolar lavage assays for the detection of GER-related aspiration. 37 In contrast, Akinola et al 38 reported no relationship between the diagnosis of BPD and the clinical diagnosis of GER confirmed by esophageal pH monitoring. 38 In a small study comparing combined MII and pH monitoring in 12 infants with BPD and 34 without who were evaluated for clinical signs believed to be attributable to GER, infants with BPD had a similar number of documented reflux events as infants without BPD.…”
Section: Respiratory Disease and Bronchopulmonary Dysplasiamentioning
confidence: 96%
“…Los beneficios y las limitaciones de estos estudios y otros exámenes complementarios se resumen en la Tabla 3. 5,10,17 Hay niños con múltiples evaluaciones negativas para disfunción de la deglución o RGE, pero con historia clínica sugestiva de aspiración y evidencia radiológica de enfermedad pulmonar; en ellos, el diagnóstico de aspiración se hace solamente cuando se ensaya la alimentación exclusiva por sonda nasogástrica y mejoran los síntomas respiratorios. 5 En los niños que continúan con síntomas de aspiración a pesar del cese de la alimentación oral y del tratamiento del No detecta RGE no ácido.…”
Section: Diagnóstico De La Aspiración De Reflujo Y De Salivaunclassified